PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, TEKANAN EKSTERNAL, KOMITMEN ORGANISASI, DAN SISTEM PENGENDALIAN INTERN TERHADAP PENERAPAN TRANSPARANSI PELAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris Pada Organisasi Perangkat Daerah Kabupaten Rokan Hilir) - Siti Puji Rahayu; Ruhul Fitrios; Sem Paulus (Department of Accounting, Faculty of Economics & Business, 2020)
Abstract: The main objective of this study is to examine the competence of human resources, external pressures, organizational commitment, and internal control systems in the implementation of financial verification in OPD Rokan Hilir using data analysis methods using Structural Equation Modelling-Partial Least Square (SEM-PLS) by using Warp-PLS version 5.0. The populationin this study are all Regional Apparaturs Organization(OPD) kabupaten Rokan Hilir. Sample selection used the slovin method as a measuring tool for calculating sample sizes. Respondent in this study are head of offices, employees in the section/unit that manages finance using the application of financial reporting transparency in 40 OPDs in the goverment kabupaten rokan hilir. So the total number of questionnaires tobe distributed is 120. The results of this study indicate that Human Resource Competency, External Pressure, Organizational Commitment, and Internal Control Systems have a positive effect on the Implementation of Transparency in Regional Government Financial Reporting